Comparação de diferentes metodologias para descelularização de veias humanas - Oliveira , Madaí Cruz Lopes de (2015)
Introduction : Non-living tissues have shown to be an important source of biomaterials, with advantages such as hydrophilicity, low toxicicidade, low immunogenicity, in addition to good adherence and cell multiplication. However, for these biomaterials to be used, techniques of descellularization is being used to make it less antigenic and also to serve as scaffolds.Objectives : The present study aims to compare different agents of descellularization regarding the above mentioned parameters, using detergents known to be effective for these processes.Materials and Methods : The samples used in this study were obtained from saphenous veins of seven individuals donors, in treatment of myocardial revascularization surgery and provided by the team of cardiovascular surgery of Hospital São Lucas da PUCRS, after signing the informed consent form.These samples were tested simultaneously three different detergents, sodium dodecyl sulfate (SDS), TRITON-X and trypsin, in addition to a control group containing Phosphate-Buffered Saline (PBS). After the process of descellularization and prior to the determination of cellularity, the samples were fixed in buffered formalin 10% during 24 hours, included in paraffin, sectioned (5 μ) and stained with hematoxylin and eosin. The number of cores was quantified in a radius of 0.025 mm (objective 40x), in duplicate, corresponding to eight fields, with the aid of the software Image Pró-Plus 4.5.1. Data were analyzed using a model of analysis of variance for repeated measures (randomized blocks) with adjustment for multiple comparisons procedure of Finner's procedure were used.Results : The results evaluated all treatments showed a decrease in the number of cells, and the SDS the agent with greater descellularization. The TRITON-X and the Trypsin obtained similar values and there was no difference between them, for this process.Conclusion : In this way, it could be demonstrated that all detergents used, and the methodology it self, acts as agentes of descellularization in human veins and proved to be a promising agents to remove cells.